Regenerated retinal ganglion cell axons can form well-differentiated synapses in the superior colliculus of adult hamsters - Carter, DA (J Neurosci, 1989)
To investigate in adult animals the distribution and differentiation of the synapses made by axotomized CNS neurons whose regenerating axons are guided back to their natural targets in the brain, we attached an autologous peripheral nerve (PN) graft 2–3 cm in length to the ocular stump of a transected optic nerve (ON) in adult hamsters, inserted the distal end of the graft into the superior colliculus (SC), and, 6–8 weeks later, labeled the retinal ganglion cell (RGC) axons that entered the SC with HRP orthogradely transported from the eye. By light microscopy, regenerated RGC axons extended from the graft into the retinorecipient layers of the SC for up to 500 microns, distances that approximate the lengths of normal RGC arbors. We compared 698 control and 758 regenerated HRP-labeled axon terminals from 4 intact and 4 experimental animals by electron microscopy. The structure of the regenerated RGC terminals, the type of synaptic contacts formed, the ratios of contacts to terminal perimeter, and the domains of the postsynaptic neurons contacted were similar to those of controls. These results indicate that regenerated RGC axons can form well- differentiated synapses in the SC. Morphological differences between the regenerated and control synapses were the larger size of some regenerated terminals, the greater mean length of the regenerated synapses, and the higher proportion of contacts with dendrites that contained vesicles. The synaptic differentiation attained by these reformed retinocollicular projections suggests that regenerating CNS axons and their target neurons in the adult mammalian brain may retain or reexpress certain molecular determinants of normal connectivity.(ABSTRACT TRUNCATED AT 250 WORDS)